Search 74,106 tutors
FIND TUTORS
Ask a question
0 0

consider the equations: f(x)= -6x-1 and g(x) =4x^2 what is the solution for (f+g)(x)?

Tutors, please sign in to answer this question.

3 Answers

(f+g)(x) = f(x) + g(x)
 
(f+g)(x) = -6*x - 1 + 4*x^2
 
(f+g)(x) =4x^2 - 6x -1
 
if you mean (f o g)(x)
 
if so
( f o g)(x) = f (g(x)) 
( f o g)(x) = f (4x^2)*******[g(x) = 4*x^2, so i just substitute it]
 
f(x)= -6x-1 , now just substitute the value of x with 4x^2
 
f(4x^2)= -6*(4x^2)-1
 
f(4x^2)= -24x^2-1
 
( f o g)(x) = -24x^2-1
 
What it is saying is add the functions together and that they are both functions of x. This is an order of operations problem. If it had said f(g(x)) Then the g function would go in place of the x's in the f function. -6(4x^2)-1. However what you are asking is for (f+g)(x)
 
So for this problem:
 
(f+g)(x)= -6x-1+4x^2
 
I'm not sure if you need to solve for x. If so you will need to use the quadratic formula.